2019
DOI: 10.1016/j.nicl.2019.101760
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated mismatch negativity in patients with first-episode antipsychotic-naive schizophrenia using a source-resolved method

Abstract: Background Mismatch negativity (MMN) is a measure of pre-attentive auditory information processing related to change detection. Traditional scalp-level EEG methods consistently find attenuated MMN in patients with chronic but not first-episode schizophrenia. In the current paper, we use a source-resolved method to assess MMN and hypothesize that more subtle changes can be identified with this analysis method. Method Fifty-six first-episode antipsychotic-naïve schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
(78 reference statements)
1
10
1
Order By: Relevance
“…As opposed to MMN amplitudes, no significant differences were observed in MMN latencies across groups either across deviant types (F (2,99) = 0.44, p = 0.65) or for any of the deviant types independently (all p > 0.2) (Table 2). As expected, there was a highly significant latency variation by deviant type (F (4,96) = 85.4, p < 0.0001) but no significant interaction with group (F (8,192) = 147, p = 0.17). The order of latencies was location < pitch < FM < duration < intensity, with significant differences between in repeated contrast testing (all p < 0.001).…”
Section: Mmn Latenciessupporting
confidence: 70%
See 1 more Smart Citation
“…As opposed to MMN amplitudes, no significant differences were observed in MMN latencies across groups either across deviant types (F (2,99) = 0.44, p = 0.65) or for any of the deviant types independently (all p > 0.2) (Table 2). As expected, there was a highly significant latency variation by deviant type (F (4,96) = 85.4, p < 0.0001) but no significant interaction with group (F (8,192) = 147, p = 0.17). The order of latencies was location < pitch < FM < duration < intensity, with significant differences between in repeated contrast testing (all p < 0.001).…”
Section: Mmn Latenciessupporting
confidence: 70%
“…Deficits in MMN generation in Sz are associated with impaired activation of superior temporal auditory cortex as reflected in both ERP source localization ( 8 , 9 ) and fMRI ( 10 , 11 ) studies, as well as reduced activation of subcortical regions such as inferior colliculus and thalamus ( 12 ). During MMN paradigms, activation is also observed within prefrontal cortex and a salience network that includes insula and anterior cingulate cortex ( 9 , 11 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced amplitude of this ERP has been consistently reported in ultra-high risk for psychosis (UHR), first-episode psychosis (FEP), and chronic schizophrenia patients, with most of the research being performed with medicated patients under passive conditions 8 15 . Two reports described reduced P3a using active paradigms in medicated patients 16 , 17 , and three studies showed P3a deficits in unmedicated patients under passive tasks 18 20 . Nevertheless, to our knowledge, no reports of P3a obtained with active paradigms in unmedicated patients have been performed (for a review on these studies see Justo-Guillén et al 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Already at the onset of disease, schizophrenia patients display abnormalities in neuroanatomical 3,4 , electrophysiological 5,6 , and cognitive measures 7 . Changes are subtle and only apparent on the group level, and antipsychotic medication as well as duration of illness are potential confounders 8,9 .…”
Section: Introductionmentioning
confidence: 99%